Voices of feminism past, present, and future - Guernsey, JoAnn Bren. (Minneapolis, MN Lerner Pub., 1996)
Traces the development of the feminist movement from the eighteenth century to the 1990s, discussing such topics as women and the vote, men's rights, and power feminism.
Keywords: Feminism -- Juvenile literature